A pre-dispatching vehicle method for a diffusion area in a 300 mm wafer fab. (16th November 2016) - Huang, Chih-Wei; Lin, James T.
Abstract: A pre-dispatching vehicle (PDV) method is proposed in this paper to improve transport performance for a diffusion area in a 300 mm wafer fabrication. The increase in demand for ultra-clean areas in semiconductor fabrication has raised the need for a more efficient automated material handling system (AMHS). A furnace tool has a long processing time of 6–12 h, thus making its operation a form-batch manufacturing step. With this application, wafer lots are stored in stockers, and delivery to furnace tools for processing is executed when the work-in-process level reaches four to six lots. Unlike current methods, where empty vehicles are sequentially dispatched for movement to load ports, the PDV method simultaneously calls several empty vehicles to move to a load port for executing transport jobs with the goal of shortening vehicle waiting time. A discrete event simulation model based on eM-Plant has been established. A simulation analysis of an AMHS for a diffusion area is conducted in detail. The results demonstrate the superiority of proposed PDV method, which substantially improves AMHS transport performance.